2015
DOI: 10.1186/s12902-015-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

Low concentrations of serum testosterone predict acute myocardial infarction in men with type 2 diabetes mellitus

Abstract: BackgroundThe aim of the present study was to investigate the associations between endogenous testosterone concentrations and the incidence of acute myocardial infarction (AMI) in men and women with and without type 2 diabetes.MethodsThe study comprised 1109 subjects ≥40 years of age (mean age 62 ± 12 years) participating in a baseline survey in Sweden in 1993–94. Information about smoking habits and physical activity was obtained using validated questionnaires. Serum concentrations of testosterone and sex hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 40 publications
(37 reference statements)
0
35
0
1
Order By: Relevance
“…In our cohort, high serum sortilin was associated with MACCE independently of hypertension, diabetes mellitus, or decreased testosterone levels - all cardiovascular risk factors. 2931 Thus, sortilin seems to be associated to MACCE risk even in individuals without these cardiovascular risk factors, suggesting that it may act through independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, high serum sortilin was associated with MACCE independently of hypertension, diabetes mellitus, or decreased testosterone levels - all cardiovascular risk factors. 2931 Thus, sortilin seems to be associated to MACCE risk even in individuals without these cardiovascular risk factors, suggesting that it may act through independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that low circulating T leads to lack of negative feedback inhibition on LH and FSH secretion, leading to primary hypogonadism. 13,16,32,33 Further to this, kisspeptin has been suggested to have the ability to increase LH pulsatility and T concentrations in T2DM males with reproductive disorders such as hypogonadism. 14,28 Dhillo and friends, 27 initially reported that the administration of exogenous kisspeptin stimulated the hypothalamic-pituitary-gonadal axis in human males causing a rise in LH, FSH and T concentrations.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, however, in the case group, LH and FSH concentrations were relatively high, although kisspeptin and T levels were low. It has been observed that low circulating T leads to lack of negative feedback inhibition on LH and FSH secretion, leading to primary hypogonadism . Further to this, kisspeptin has been suggested to have the ability to increase LH pulsatility and T concentrations in T2DM males with reproductive disorders such as hypogonadism .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has emerged over the last 20 years that ED and TD are important predictors of increased cardiovascular risk but while ED is widely accepted as a “marker”, the position of TD remains controversial . Recent evidence demonstrates that ED and TD may be useful and relevant in terms of early diagnosis of CVD and effective management to target risk reduction …”
Section: Low Testosterone a Risk Factor Or Risk Marker—the Clinical mentioning
confidence: 99%